Journal of peace research
Journal of Peace Research (JPR) is an interdisciplinary and international peer reviewed bimonthly journal of scholarly work in peace research. Journal of Peace Research strives for a global focus on conflict and peacemaking. The journal encourages a wide conception of peace, but focuses on the causes of violence and conflict resolution. This journal is a member of the Committee on Publication Ethics (COPE).